Пираты Гибралтара - Трофимов Ерофей (Городская проза, 2020)
Экземпляры: Камская библиотека (20220606) / Инвентарный номер: 13802 / Цена: / Сис.шифр: 84(2=411.2)6 / Авт.знак: Т 76 / ББК: 84(2=411.2)6-445.1